Knee osteotomy combined with meniscal allograft transplantation versus knee osteotomy alone in patients with unicompartmental knee osteoarthritis: a prospective double-blind randomised controlled trial protocol - Stefano Zaffagnini; Giuseppe Filardo; Marco Miceli; Angelo Boffa; Alessandro Di Martino; Gina Lisignoli; Lorenzo Zanasi; Luca De Marziani; Claudio Belvedere (BMJ Open)
Introduction Knee osteotomy combined with meniscal allograft transplantation (MAT) showed promising results to treat unicompartmental knee osteoarthritis (OA) secondary to meniscal deficiency and knee malalignment. However, there is still no high-level evidence to demonstrate whether the combination of these two treatments is superior to osteotomy alone.Methods and analysis 52 patients with unicompartmental knee OA Kellgren-Lawrence grade ≤3 secondary to meniscal deficiency and knee malalignment (aged 20–60 years) are randomised to undergo knee osteotomy associated with MAT or knee osteotomy alone in a 1:1 ratio. The primary outcome is the International Knee Documentation Committee (IKDC) subjective score at 12 months. The secondary outcomes are the IKDC subjective score at 1, 3 and 6 months, the Western Ontario and McMaster Universities Osteoarthritis Index score, the Knee Injury and Osteoarthritis Outcome Score, the Visual Analogue Scale, the EuroQol Visual Analogue Scale, the Tegner Activity Level Scale, objective parameters (transpatellar circumference, suprapatellar circumference and range of motion), patient expectation on treatment efficacy and patient satisfaction at 1, 3, 6 and 12 months. Radiographs are performed at baseline and at 1-, 6- and 12-month follow-ups and magnetic resonance evaluations at baseline and at 12 months. Biomechanical assessment is performed through gait analysis before surgery and at 12 months, investigating motion data, biomechanical parameters and muscle activation through electromyography. In addition, to detect early joint environment changes and potential MAT effects in protecting the articular surface providing a better knee homeostasis, biological markers of cartilage turnover and inflammation obtained from synovial fluid, serum and urine are evaluated at baseline and at 24 hours, 1-, 3-, 6- and 12-month follow-ups.Ethics and dissemination The study protocol has been approved by Emilia Romagna’s Ethics Committee (CE-AVEC), Bologna, Italy. Written informed consent is obtained from all participants. Findings of this study will be disseminated through peer-reviewed publications and conference presentations.Protocol version March 2023.Trial registration number NCT05840887.